(untitled) (Fiep Bulletin - online, 2019)
ABSTRACT: The present study had as main objective to understand the occurrence of premature birth in a privatematernity hospital, and as specific objectives to identify the most frequent risk factors, as well as to identify the profile of thepatients who developed this condition. The search for premature birth causes should assist the prevention of its occurrence,considering that the clinical treatment may be ineffective. It is important to emphasize that the search for a better way to inhibit thepremature birth is still the most favorable treatment, provided that the chance of development and survival of the prematurenewborn is really small. This was a documental study, using as a secondary data source the electronic medical records of 97patients who developed a premature birth in the period between July and December 2014. The data collection instrument was a24-variable questionnaire. A larger occurrence of the elective premature birth was identified, corresponding to 58% of the sample,76% were patients with a gestational age between 32 and 36 weeks, almost 90% of the sample did not have a previous abortionrecord and 81% were pregnant for their first time. The risk factors found by the study represent the large complexity in theevaluation of risk for premature birth and stress the importance in their identification in order to improve the development of thegestation with no complications.